2015
DOI: 10.1021/ja512388n
|View full text |Cite
|
Sign up to set email alerts
|

Solvent and Temperature Probes of the Long-Range Electron-Transfer Step in Tyramine β-Monooxygenase: Demonstration of a Long-Range Proton-Coupled Electron-Transfer Mechanism

Abstract: Tyramine β-monooxygenase (TβM) belongs to a family of physiologically important dinuclear copper monooxygenases that function with a solvent-exposed active site. To accomplish each enzymatic turnover, an electron transfer (ET) must occur between two solvent-separated copper centers. In wild-type TβM, this event is too fast to be rate limiting. However, we have recently shown [Osborne, R. L.; et al. Biochemistry2013, 52, 1179] that the Tyr216Ala variant of TβM leads to rate-limiting ET. In this study, we presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…Finally, ascorbic acid binds to the substrate intermediate, triggering the release of the product. However, although a recent study on TBH has demonstrated a proton-coupled long-range electron transfer mechanism ( 41 ), one of the more difficult things to appreciate is how the necessary electron transfer proceeds over a distance of more than 10 Å with the lack of domain movement ( 25 , 26 ). The DBH structure indicates that maybe domain movement places the two copper sites close together during the electron transfer step.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, ascorbic acid binds to the substrate intermediate, triggering the release of the product. However, although a recent study on TBH has demonstrated a proton-coupled long-range electron transfer mechanism ( 41 ), one of the more difficult things to appreciate is how the necessary electron transfer proceeds over a distance of more than 10 Å with the lack of domain movement ( 25 , 26 ). The DBH structure indicates that maybe domain movement places the two copper sites close together during the electron transfer step.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative hypothesis for the ET pathway of the catalytic electron has recently been suggested from studies on the TBM system. Unlike the TBM Y216W/I variants, the TBM Y216A mutant shows rate-limiting electron transfer (27), which has allowed the deuterium solvent isotope effect on this rate constant to be determined (40). The size of this isotope effect and its T-dependence indicate a large entropic contribution to the driving force, suggesting solvent reorganization as a critical step in the catalytic ET process.…”
Section: Discussionmentioning
confidence: 99%
“…A number of proposals for the catalytic ET step have been advanced. These have included superoxide channeling (38); a “substrate-mediated” pathway involving H108, Q170, a water molecule, and the peptide substrate; direct interaction of the Cu(I)H with the substrate radical via domain movement (39); and transfer across the inter-site cavity via an ordered array of water molecules, perhaps assisted by Y79 (26, 27, 40). However, these mechanisms do not account for all of the available data.…”
mentioning
confidence: 99%
“…An exciting collaboration between Dale Edmondson at Emory University and Mitch Brenner in my laboratory led to the important discovery that DβM requires two uncoupled copper ions per active site to function (12); this finding was followed by single-turnover, rapid mixing experiments to show that both of the (prereduced) copper centers undergo rapid reoxidation in a single phase that correlates with the time constant for the formation of norepinephrine from dopamine (13). The presence of two uncoupled copper centers was later confirmed by X-ray crystallography (14), introducing the new challenge of understanding how spatially distant copper centers separated by solvent water molecules are capable of supporting a highly controlled oxygen insertion into dopamine (15,16), in the absence of any of the uncoupling reactions (17) commonly seen in monooxygenases. Our most recent proposal of a long-range proton-coupled electron transfer (PCET) ( 16) is relevant to many biological processes and has emerged as a highly active research area at the interface of theory and experiment.…”
Section: Early Years At Uc Berkeleymentioning
confidence: 99%
“…As with hydrogen and its three isotopes (H, D, and T), oxygen also offers three isotopes ( 16 O, 17 O, and 18 O) as mechanistic probes. Although our primary focus was, over many years, the comparison of 16 O with 18 O, an early study made use of all three oxygen isotopes in the context of looking for alternative explanations to the huge (nonclassical) KIEs first seen in the lipoxygenase reaction.…”
Section: Oxygen Activationmentioning
confidence: 99%